1998
DOI: 10.1101/gad.12.15.2345
|View full text |Cite
|
Sign up to set email alerts
|

A novel homeobox gene, dharma, can induce the organizer in a non-cell-autonomous manner

Abstract: The formation of Spemann organizer is one of the most important steps in dorsoventral axis determination in vertebrate development. However, whether the organizer forms autonomously or is induced non-cell-autonomously is controversial. In this report we have isolated a novel zebrafish homeobox gene, dharma, capable of inducing the organizer ectopically. The expression of dharma was first detected in several blastomeres at one side of the margin soon after the mid-blastula transition and continued in the dorsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 44 publications
1
128
0
Order By: Relevance
“…2E). A loss of posterior structures also occurs in dorsalized embryos, as caused by the loss of Bmp signaling (Mullins, 1999) or by overexpression of boz (Yamanaka et al, 1998;Koos and Ho, 1998). Like in embryos injected with boz mRNA, but unlike in bmp mutants, admp morphant embryos display a significant enlargement of the organizer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2E). A loss of posterior structures also occurs in dorsalized embryos, as caused by the loss of Bmp signaling (Mullins, 1999) or by overexpression of boz (Yamanaka et al, 1998;Koos and Ho, 1998). Like in embryos injected with boz mRNA, but unlike in bmp mutants, admp morphant embryos display a significant enlargement of the organizer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of the YSL is one of the earliest differentiation events in the embryo and plays a vital role in embryo development: The YSL is crucial in regulating dorso-anterior axis formation (2)(3)(4)(5)(6), epiboly movements involved in embryo patterning and morphogenesis (7)(8)(9)(10)(11)(12), and cardiac progenitor cell movements (13).…”
mentioning
confidence: 99%
“…␤-catenin cooperates with the HMG-box factor Tcf/Lef in activating the expression of some dorsal-specific genes, such as bozozok/dharma (boz) in zebrafish. Boz, directly regulated by ␤-catenin, is a transcriptional repressor, and its downstream targets include several genes that induce ventral specification or inhibit dorsal development (Yamanaka et al, 1998;Fekany et al, 1999;Koos and Ho, 1999). The zebrafish boz mutant shows defects in dorsoanterior embryonic structures and it has been reported that this factor promotes development of anterior neuroectoderm by inhibiting BMP and Wnt signaling (Solnica-Krezel and Driever, 2001).…”
Section: Introductionmentioning
confidence: 99%